2015
DOI: 10.3390/ijms16048310
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reference Genes for MicroRNA Quantitative Expression Analysis in Chinese Perch, Siniperca chuatsi

Abstract: Real-time quantitative reverse transcription PCR (RT-qPCR) is one of the most effective and sensitive techniques in gene expression assay, for which selection of reference genes is a prerequisite. In teleost species, such as Chinese perch, the expression profiling of miRNAs as reference genes for RT-qPCR has not been intensively studied. In the present study, the expression profiles of six miRNAs (miR-101a, miR-146a, miR-22a, miR-23a, miR-26a and let-7a) and one small nuclear RNA (U6) were assayed with RT-qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…The validation of reference genes in our study indicated that three miRNAs, either gmo -17-1—5p alone, or the combination of gmo -miR-25-3p and gmo -miR-210-5p, were particularly suitable as reference genes in Atlantic cod. In agreement with recent finding in similar studies [ 58 ] U6 performed less well compared to the miRNAs as an endogenous control. MiR-25-3p seems to perform well as a miRNA reference gene in several teleosts [ 37 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…The validation of reference genes in our study indicated that three miRNAs, either gmo -17-1—5p alone, or the combination of gmo -miR-25-3p and gmo -miR-210-5p, were particularly suitable as reference genes in Atlantic cod. In agreement with recent finding in similar studies [ 58 ] U6 performed less well compared to the miRNAs as an endogenous control. MiR-25-3p seems to perform well as a miRNA reference gene in several teleosts [ 37 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…found that miR-101a was the most stable miRNA when all tissue types were considered separately [ 63 ]. In Siniperca chuatsi , all six miRNAs (miR-101a, miR-146a, miR-22a, miR-23a, miR-26a and let-7a) exhibited better expression consistency than U6 in most of the conditions examined, and the best combination of reference genes was miR-22a and miR-23a [ 64 ]. Herein, we systematically evaluated the reliability of seven miRNA genes across 15 tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the Illumina sequencing, 10 conserved miRNAs that have been reported with relative stable expression in other organisms [ 45 47 ] and 10 novel identified miRNAs with high abundance in sRNA library of G . molesta ( S1 Table ) were selected and their expression level in the sample for construction of sRNA library were checked using qPCR.…”
Section: Methodsmentioning
confidence: 99%